2011
DOI: 10.1387/ijdb.103109rk
|View full text |Cite
|
Sign up to set email alerts
|

Targeted expression of p35 reveals a role for caspases in formation of the adult abdominal cuticle in Drosophila

Abstract: Programmed cell death is a fundamental aspect of metazoan development associated with the elaboration of disparate tissues and structures. Specialized cysteine proteases, the caspases, are mediators of cell death; once activated they cleave substrate proteins to dismantle doomed cells. Caspase activity is regulated by several cellular and viral inhibitors. The baculovirus p35 protein blocks the action of a wide range of caspases and inhibits cell death in divergent species. Here, we utilize the Gal4/UAS system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…A large number of experimental studies have shown that caspase-3 plays an important role in the pathological process of myocardial and cerebral ischemia. It has attracted a great deal of attention, mainly for its role in the final common pathway of apoptosis (Yu et al, 2006;Kester and Nambu, 2011). The results of this study showed that the expression level of caspase-3 mRNA decreased significantly after the P35 protein was injected into the rats with ACI, which further confirms that the P35 protein has a certain inhibitory effect on the apoptosis pathway of brain tissue in rats following treatment.…”
Section: Discussionsupporting
confidence: 69%
“…A large number of experimental studies have shown that caspase-3 plays an important role in the pathological process of myocardial and cerebral ischemia. It has attracted a great deal of attention, mainly for its role in the final common pathway of apoptosis (Yu et al, 2006;Kester and Nambu, 2011). The results of this study showed that the expression level of caspase-3 mRNA decreased significantly after the P35 protein was injected into the rats with ACI, which further confirms that the P35 protein has a certain inhibitory effect on the apoptosis pathway of brain tissue in rats following treatment.…”
Section: Discussionsupporting
confidence: 69%
“…To identify the photoreceptor defects were caused by inappropriate activation of apoptosis, we employed p35 to suppress apoptosis; P35 is cleaved and forms a thioester bond with the caspase active site, thereby causing irreversible inhibition of the caspase[42]. Furthermore, p35 effectively inhibits a broad range of active caspases and can block cell death [43]. We used the MARCM system to over-express p35 in the usp5 mutant clones.…”
Section: Resultsmentioning
confidence: 99%
“…During metamorphosis, tergites and male genitalia development requires apoptosis [ 41 45 ]. Consistently, mutations in apoptotic genes such as Drice , or overexpression of the apoptosis inhibitors P35 or Diap1 in tergite and genitalia anlage, give rise to adult flies presenting cuticle midline and genitalia rotation defects [ 41 ]. To test if PGRP-LF mutant phenotypes are due to apoptosis inhibition in ectodermal anlage, we overexpressed P35 in PGRP-LF expression domain.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, neither loss-of function of PGRP-LF nor gain-of-function of IMD were able to activate pro-apoptotic Hid or Reaper transgenic reporter constructs in these tissues ( S10A–S10C Fig ). We could also showed that Diap1 ectopic expression using either a ubiquitous Gal4 ( Act5C Gal4 ) or PGRP-LF Gal4 drivers was sufficient to mimic both cuticle and genitalia defects ( S7C Fig ) [ 41 ]. Altogether these results show that by preventing IMD pathway activation in ectodermal derivatives, PGRP-LF is allowing normal cell death to occur and pupal development to proceed.…”
Section: Resultsmentioning
confidence: 99%